THE ROLE OF THE JALILTEPA SETTLEMENT IN THE CULTURES OF THE ANCIENT FERGHANA VALLEY (by archives materials) (Scientific journal of the Fergana State University, 2023)
The article presents the scientists who conducted archaeological research in the Fergana Valley and their proposals on the periodization of the history of the valley. Also, based on the results of the conducted archaeological researches, various pottery vessels found around the "Jaliltepa" settlment were comparatively analyzed and the period of the settlment was specified. According to this study, the period of the "Jaliltepa" settlment was determined as II-VII centuries BC.